(3Odjd GdOYe GdfaSj GdGLJeGYj GKfGA hHYO GdGReGJ s
(3gPG GdcJjH ehLg Gdi GdeTQajf hGdeYdejf hLejY GdYGedjf eY GdGWaGd(B. (3Gfg jhaQ OYe faSj JhLjgj fGaY aj GjI HjFI JhaQ GdQYGjI ddGWaGd(B.s
Sommaire.
Keywords: Psychosociologie; Traumatisme psychique